TRANSMISSIBLE VENEREAL TUMOR: CELL PROLIFERATION (AGNOR) AND RESPONSE TO CHEMOTHERAPY CORRELATED WITH CYTOMORPHOLOGICAL CLASSIFICATION - REIS FILHO, N. P.; TORRES, A. A. A.; SILVA, M. P. C.; VENTURA, R. F. A.; BASSO, K. M.; FERREIRA, M. G. P. A.; DE NARDI, A. B.; FLORIANO, B. P.; CALDERÓN, C. (Ars Veterinaria, 2020)
Transmissible venereal tumor (TVT) is a contagious neoplasm of round cells that occurs naturally and that affects mostly the genitalia. The TVT has been classified according to the predominant cell type as follows: linfocytoid, plasmacytoid and mixed. Various degrees of aggressiveness with wide range of biological behavior have been described based on this cell morphology. The present study aimed to evaluate the rate of cell proliferation, by cytochemical AgNOR method, and response to chemotherapy correlated with the cytomorphological classification of TVT. The results of the 22 cases showed that TVT was identified more frequently in female, adults and mixed-breed dogs. Plasmocytoid-classified tumors required a greater number of vincristine sulfate sessions, have higher cell proliferation and were the most resistant to chemotherapy, requiring additional treatment with doxorubicin. Based on these results, we can infer that the plasmacytoid pattern might have a more aggressive behavior compared to other cell types.